2015
DOI: 10.1128/mbio.00235-15
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Parasites Produce Volatile Mosquito Attractants

Abstract: The malaria parasite Plasmodium falciparum contains a nonphotosynthetic plastid organelle that possesses plant-like metabolic pathways. Plants use the plastidial isoprenoid biosynthesis pathway to produce volatile odorants, known as terpenes. In this work, we describe the volatile chemical profile of cultured malaria parasites. Among the identified compounds are several plant-like terpenes and terpene derivatives, including known mosquito attractants. We establish the molecular identity of the odorant receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 47 publications
2
44
0
1
Order By: Relevance
“…When paired with quantitative trait locus (QTL) analysis, metabolo-mic profiling has revealed that peptide accumulation mediates fitness costs associated with chloroquine resistance (51). Additionally, metabolomics has aided in the elucidation of novel elements of Plasmodium biology, such as the production of plant-like terpenes through the isoprenoid biosynthesis pathway (56), the availability of a diverse pool of host metabolites in reticulocytes compared to mature erythrocytes (57), and rapid arginine depletion in vitro, which may be the basis for clinical hypoargininemia (54). More recently, a number of studies have utilized untargeted metabolomics analysis to characterize the mode of action of drugs in other related parasites (58,59).…”
mentioning
confidence: 99%
“…When paired with quantitative trait locus (QTL) analysis, metabolo-mic profiling has revealed that peptide accumulation mediates fitness costs associated with chloroquine resistance (51). Additionally, metabolomics has aided in the elucidation of novel elements of Plasmodium biology, such as the production of plant-like terpenes through the isoprenoid biosynthesis pathway (56), the availability of a diverse pool of host metabolites in reticulocytes compared to mature erythrocytes (57), and rapid arginine depletion in vitro, which may be the basis for clinical hypoargininemia (54). More recently, a number of studies have utilized untargeted metabolomics analysis to characterize the mode of action of drugs in other related parasites (58,59).…”
mentioning
confidence: 99%
“…Increases were broadly associated with infections with high malaria parasite load, compared to patients having either low malaria parasite density or being parasite-free [44]. Kelly et al [45] reported that P. falciparum infected erythrocytes released few VOCs under in vitro culture conditions. Amounts of the monoterpene, α-pinene, were higher in the samples containing erythrocytes infected by P. falciparum strain 3D7-MR4 at 2% parasitemia compared to those bearing uninfected erythrocytes as well as to the samples containing infected erythrocytes treated with 5 µM of fosmidomycin [45], an inhibitor of parasite isoprenoid biosynthesis by affecting the first enzyme of the MEP pathway, deoxyxylulose phosphate reductoisomerase [46,47].…”
Section: Plasmodium Induced Volatile Organic Compounds (Vocs) and Mosmentioning
confidence: 99%
“…Kelly et al [45] reported that P. falciparum infected erythrocytes released few VOCs under in vitro culture conditions. Amounts of the monoterpene, α-pinene, were higher in the samples containing erythrocytes infected by P. falciparum strain 3D7-MR4 at 2% parasitemia compared to those bearing uninfected erythrocytes as well as to the samples containing infected erythrocytes treated with 5 µM of fosmidomycin [45], an inhibitor of parasite isoprenoid biosynthesis by affecting the first enzyme of the MEP pathway, deoxyxylulose phosphate reductoisomerase [46,47]. Identification of other four compounds, namely, 3,5-bis (1,1-dimethylethyl)-4-methyl-1H-pyrazole, 6-hydroxy-5,7-dimethoxynaphtho[2,3-c]furan-1(3H)-one, 4,5,9,10-dehydroisolongifolene and 8,9-dehydro-9-formyl cycloisolongifolene is putative, due to insufficient match factors of mass spectra obtained from analytes and those available in electronic libraries as well as the absence of standards during identification [45].…”
Section: Plasmodium Induced Volatile Organic Compounds (Vocs) and Mosmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of purified odorants from these plants has revealed enrichment of volatile compounds known as terpenes, including 10-carbon monoterpenes such as pinene and limonene, which at low concentrations have been shown to mediate attraction of Anopheles spp. [94,95]. Several approaches are currently available for oral delivery to mosquitoes by droplet or liquid feeding, through dry diets [96], or via nylon strips continuously dispensing synthetic mosquito attractants for several weeks [97,98].…”
Section: Direct Antimalarial Drug Administration To Mosquitoesmentioning
confidence: 99%